The Gift of Restlessness A Spirituality for Unsettled Seasons. - Tygrett, Casey (1517 Media, 2023)
In seasons of unsettledness, is the best way forward to quickly resolve the questions? In The Gift of Restlessness, spiritual director Casey Tygrett excavates the questions at the root of unsettledness: Where do I belong? What am I here for? Is there enough? Tygrett shows us that restlessness is normal, healthy, and even holy.